TACOS: TESS AM CVn Outbursts Survey. Issue 3 (21st September 2021) - Pichardo Marcano, Manuel; Rivera Sandoval, Liliana E; Maccarone, Thomas J; Scaringi, Simone
ABSTRACT: Using Transiting Exoplanet Survey Satellite ( TESS ), we are doing a systematic study of outbursting AM CVn systems to place some limits on the current outbursts models. We present the TESS light curve (LC) for 9 AM CVns showing both superoutbursts (SOs) and normal outbursts (NOs). The continuous coverage of the outbursts with TESS allows us to place stringent limits on the duration and structures of the SOs and the NOs. We present evidence that in at least some of the systems enhanced mass transfer (EMT) has to be taken into account to explain the observed LC of the SOs and rebrighthening phase after the SOs. For others, the colour evolution from simultaneous observations in g and r with ZTF differs from previously reported colour evolution of longer period AM CVns where EMT is responsible for the SO. We also find that due to the lack of sufficiently high cadence coverage the duration of many systems might have been overestimated in previous ground-based surveys. We report the SO duration for 6 AM CVns. We also found that precursors are a common feature of SOs in AM CVns and are seen in the LC of 5 of the 6 reported SOs. Finally, the 10-min and 2-min cadence LCs from TESS also allowed us to find two new candidate orbital periods of AM CVns, both of which are in reasonably good agreement with the predictions for their periods based on their past outburst histories.